E-health literacy status and its influencing factors among college students majoring in sports - Yue Yin; Jing Chen; Wenqing Zhao; Linwang Hu; Hang Cai; Liang Gao (Frontiers in Public Health, 2026)
Objective To understand the level of e-health literacy among sports majors and its influencing factors, providing reference for developing measures to improve e-health literacy in this population. Methods An online survey was conducted among college students from 6 universities in Jiangsu Province using an e-health literacy questionnaire. SPSS 26.0 statistical software was used for χ 2 test. t -test, one-way ANOVA, and multiple linear regression analysis were employed to explore the influencing factors of e-health literacy level. Results Among the 923 respondents, 722 (78.2%) were male and 201 (21.8%) were female. The average e-health literacy score was 41.91 ± 6.90, with an adequate rate of 22.2% (205 individuals). Influencing factor analysis showed that ethnicity (95%CI: −3.641 ~ −0.408), gender (95%CI: 1.292 ~ 3.445), self-rated health status compared with peers (95%CI: −1.276 ~ −0.100), use of smart wearable devices (95%CI: 0.100 ~ 0.794), harmony with surrounding people (95%CI: 0.379 ~ 1.733), frequency of searching health knowledge on the Internet (95%CI: 0.246 ~ 1.099), computer proficiency (95%CI: 0.230 ~ 1.569), days waking up feeling energetic in the morning (95%CI: 0.188 ~ 1.207), frequency of consuming fish, poultry, meat and eggs (95%CI: 0.194 ~ 1.331), and types of health knowledge content searched (95%CI: 0.023 ~ 1.556) were significant factors affecting e-health literacy among college students. Conclusion The e-health literacy level of sports majors is relatively low, with associated factors spanning multiple dimensions. Targeted interventions should prioritize male students, those with poorer self-rated health, and those with weaker interpersonal relationships. Strengthening digital skills and active information practice is a key strategy for improving e-health literacy in this population.